ACCIDENTS DUE TO DRUNKEN DRIVING IN TRIBAL CULTURE AND PREDICTIVE DEPLOYMENT OF POLICE - Rohit Malpani, IPS & Anubhav Sinha (International Journal of Research Science and Management, 2016)
India is a signatory to Brasilia Declaration and is committed to reduce the number of road accidents and fatalities by 50 per cent by 2020. The task of reducing fatalities in accidents in tougher in mountainous terrain compared to the plains due to risky terrain, structural faults in road engineering, difficult annual maintenance, traffic congestion on hilly roads, ignorance of hilly people and drinking habits i.e. drunken driving habits among the tribals. This paper deals with specific issues related to high fatality rate in accidents in extreme hilly district of Kinnaur (Himachal Pradesh) and possible solutions using technology i.e. Google Maps which can be replicated in other hilly districts of India too.